(untitled) (Medical Forum Monthly, 2024)
Objective: To evaluate the frequency of Hepatitis B & C in patients receiving some sort of Dental Procedures in Dentistry Department of KGN Teaching Hospital, Bannu-KPK Pakistan. Study Design: Descriptive/cross sectional study Place and Duration of Study: The study was conducted in Dental Block, KGN Teaching Hospital, Bannu-KPK Pakistan from 1st January 2018 to 30thJune 2018. Materials and Methods: 198 patients were included in the study who came to dentistry department, KGN hospital Bannu for numerous types of dental procedures. Serum of these 198 patients was screened and examined for the detection of HCV Ag and HBV Ag. Rapid card diagnostic test was performed for the same. Among all these 200 samples, all rapid test positive samples were tested further by ELISA. Data was analyzed statistically using one way ANOVA. Results: Among dental patients, the overall HBV and HCV sero prevalence was found to be 4.0% and 4.5% correspondingly. Only 1.2% patients had both the infections. No remarkable difference was observed in prevalence of HBV and HCV in both genders i.e. male and female. An increased prevalence was found in patients having an age 52-62 years (11% for HBV and HCV respectively). Among the positive patients, most were belonging to Domail and Link road Bannu area. A high prevalence of dental procedure was found in patients in comparison to control (p≤0.001) for both HCV and HBV. Conclusion: The sero-frequency of HCV and HBV is greater in rural area of district Bannu. This high frequency is attributed to the dentistry malpractice which is being carried out in these areas. We recommend that inhabitants of the rural areas should make their regular checkup for both hepatitis B & C in order to avoid the disease.